1994
DOI: 10.3109/00952999409084060
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 among Inner City Dually Diagnosed Inpatients

Abstract: The objectives of this study were to investigate HIV-1 seroprevalence and risk factors, disease progression, and awareness of HIV-1 serostatus in a population of inner city, substance using, psychiatric inpatients. To pursue these goals, we tested 118 (103 M, 15 F) dually diagnosed, acute care inpatients for HIV-1 antibodies and administered structured interviews. Twenty-seven (23%, including 24 M and 3 F) of the subjects were HIV-1 seropositive. Seropositivity was twice as great among intravenous drug users a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(42 citation statements)
references
References 13 publications
3
39
0
Order By: Relevance
“…Many studies on the association between schizophrenia and the human immunodeficiency virus (HIV) positivity were found. Although the prevalence of HIV positivity in people with schizophrenia was generally higher than in the general population (0.6% in the general population of America according to a WHO statistic) (21), the prevalence varied substantially [1.3-22.9% (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)]. This variability probably reflects a different degrees of prevalence of HIV positivity in different parts of the world.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies on the association between schizophrenia and the human immunodeficiency virus (HIV) positivity were found. Although the prevalence of HIV positivity in people with schizophrenia was generally higher than in the general population (0.6% in the general population of America according to a WHO statistic) (21), the prevalence varied substantially [1.3-22.9% (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)]. This variability probably reflects a different degrees of prevalence of HIV positivity in different parts of the world.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies found that HIV risk behaviours are associated with severity of mental health disability (Rosenberg et al, 2005;Heaphy et al, 2010), although a third study did not find any significant associations with different mental health disabilities (Collins et al, 2009). Depression and post-traumatic stress disorder were also found to be associated with higher HIV risk (Hoff et al, 1997;Silberstein et al, 1994).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 92%
“…[1] Estimates from samples during the 1990s suggest that the prevalence of HIV among individuals with SMI ranges from 3-23%. [2][3][4][5][6][7][8][9][10] Highly active antiretroviral therapy (HAART) has revolutionized the treatment of HIV leading to significant declines in HIV related morbidity and mortality as well as declines in hospitalization. [11][12][13][14][15][16][17] Although previous studies suggest that individuals with SMI are less likely to receive potentially life saving interventions for non-HIV-related chronic conditions, [18;19] few studies have evaluated the degree to which HIV infected individuals with SMI receive HAART.…”
Section: Introductionmentioning
confidence: 99%